Microsatellite Status Affects Tumor Response and Survival in Patients Undergoing Neoadjuvant Chemotherapy for Clinical Stage III Gastric Cancer - Cai, Zhenghao; Rui, Weiwei; Li, Shuchun; Fingerhut, Abraham; Sun, Jing; Ma, Junjun; Zang, Lu; Zhu, Zhenggang; Zheng, Minhua (Frontiers in Oncology, 2020)
Background: We assessed the association between microsatellite instability-high (MSI-H) and tumor response to neoadjuvant chemotherapy (NAC) as well as its prognostic relevance in patients with clinical stage Ⅲ gastric cancer (cStage Ⅲ GC). Materials and Methods: The NAC + surgery and the control cohorts consisted of 177 and 513 cStage Ⅲ GC patients, respectively. The clinical and pathological features were compared between patients with MSI-H (n=57 (8.3%)) and microsatellite stability or microsatellite instability-low (MSS/MSI-L) (n=633 (91.7%)). Radiological and histological response to NAC were evaluated based on response evaluation criteria in solid tumors (RECIST) and tumor regression grade (TRG) systems, respectively. The log-rank test and Cox analysis were used to determine the survival associated with MSI status as well as tumor regression between the two groups in both NAC + surgery and the control cohorts. Results: A statistically significant association was found between MSI-H and poor histological response to NAC (p=0.038). Significant survival priority of responders over poor-responders could only be observed in MSS/MSI-L but not in MSI-H tumors. However, patients with MSI-H had statistically significantly better survival compared to patients with MSS/MSI-L in both the NAC + surgery (hazard ratio=0.125, 95% CI, 0.017-0.897, p=0.037 ) and the control cohort (hazard ratio=0.479, 95% CI, 0.268-0.856, p=0.013). Conclusion: MSI-H was associated with poorer regression and better survival after NAC for cStage Ⅲ GC. TRG evaluation had prognostic significance in MSS/MSI-L but not in MSI-H. Further studies are needed to assess the value of NAC for cStage Ⅲ GC patients with MSI-H phenotype.